Illustration in Explanatory Dictionary - Feraj, Asime; Albania, Arjan Llanaj (European Journal of Multidisciplinary Studies, 2017)
This paper has treated the syntagmatic level in the explanatory dictionaries, in the monolingual and bilingual as well, since the syntagmata in the dictionary can be dealt with as being unnoticed, because it is considered as less important than explanations or definitions or equivalents (when the dictionary is bilingual). But, if, for example, it can’t be said in the explanation that a verb or adjective can be linked with words that refer to alive and not alive objects, than the user can see the illustrative examples (the weather became cold/cold (distant) from his friend; a cold room/a cold person; a man walks/ the horse walks ; the time passes/ the work goes on; ecën koha (ecën puna). Nowadays, when the society is developing so fast and thoroughly, the use and utilisation of monolingual, bilingual, multilingual, linguistic or encyclopaedic dictionaries, is the most common and inevitable phenomenon, because these works not only are recorders of the word and phraseology, of semantic and lexical fortune, national and international one, but also have their determining importance in the acquirement of the language and in the expansion of the linguistic and communicative competence, in finding an unknown word and its semantic definition, or in finding lexical and semantic units with which creates semantic, paradigmatic, word-forming and stylistic relations etc. The illustrative examples are helpful for the full exploration of meaning and serve as an additional instrument for the characterisation of the word, showing the area of use and the typical grammatical lexicon enclosure. They also prove the stylistic evaluation and grammatical characteristic that is given to the word. The main purpose of this paper is that by relying in the subject that is offered by these kind of irreplaceable works, it will treat the importance of the syntagmatic level of the explanatory dictionary as an important part for knowing the word and its significance, to increase the lexical and semantic competence of the users of these dictionaries.
Keywords: dictionary, explanation of meaning, syntagmatic link, utterances, examples.